Sexual scripts in Polish and German adolescents = Skrypty seksualne u młodzieży w Polsce i w Niemczech - Tomaszewska, Paulina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents an analysis of cognitive scripts for consensual sexual interactions among Polish and German adolescents. Two types of sexual scripts were investigated, such as the individual script, which refers to the characteristic elements of sexual interaction with a new partner with regard to one`s own standards, cognitions, and experiences; and the general script, which considers the age group as a whole.
Keywords: młodzież; skrypty seksualne; kontakty seksualne; role płciowe; badania międzykulturowe; youth; sexual scripts; sexual contacts; gender roles; intercultural studies